Primate antibody response to immunotoxin: Serological and computer-aided analysis of epitopes on a truncated form of Pseudomonas exotoxin - Donna M. Roscoe; 정선희; Itai Benhar; Lee Pai; Byungkook Lee; Ira Pastan (1994)
NLysPE38 is a 38-kDa derivative of Pseudomonas exotoxin (PE) in which domain Ia (amino acids 1 to 252) and part of domain Ib (365 to 380) are deleted and an 11-amino-acid N-terminal peptide is added. LMB-1 is an immunotoxin in which the monoclonal antibody B3 is coupled to NLysPE38 near its N terminus. LMB-7 is a single-chain immunotoxin in which the Fv fragment of B3 is fused to PE38. To identify the antigenic regions of PE38, 12 polyclonal serum samples from monkeys immunized with the immunotoxins LMB-1 (six monkeys) and LMB-7 (six monkeys) were tested for their reactivity to a panel of 120 synthetic, overlapping peptides representing the amino acid sequence of NLysPE38. The antibody responses to peptides were similar among the 12 serum specimens, identifying several major immunodominant B-cell epitopes. Predominant reactivity was seen in six locations: amino acids 272 to 287, 341 to 359, 504 to 516, 540 to 564, and 573 to 591 and the C-terminal amino acids 591 to 613. The sera did not react with approximately 75% of the peptides. Furthermore, a computer-aided analysis was done to predict the immunologically relevant areas and revealed the same antigenic regions defined by serum reactivity to peptides. Competition enzyme-linked immunosorbent assays and neutralization assays were performed with domain II, III, or III plus Ib of PE38 and confirmed the immunodominance of domain III. To analyze the role of specific amino acids in antibody binding, individual amino acids of PE38 with large accessible surface areas were altered by site- directed mutagenesis. These results also show that the predicted areas of immunogenicity agree with the reactivity of the anti-PE38 antibodies to peptides and to the mutants of PE.